T2 Gallbladder Cancer—Aggressive Therapy is Warranted. Issue 6 (June 2016) - Sheikh, Mohd Raashid; Osman, Houssam; Cheek, Susannah; Hunter, Shenee; Jeyarajah, Dhiresh Rohan
Treatment of gall bladder cancer (GBC) has traditionally been viewed with pessimism and lymph node positivity has been associated with worse prognosis. The aim of this study is to analyze the role of radical cholecystectomy in T2 tumors. All patients who underwent surgery for GBC between September 2005 and June 2014 were identified retrospectively. Data collected included clinical presentation, operative findings, and histopathological data. Twenty-five patients had incidental GBC diagnosis after cholecystectomy. Ten patients were T2 on initial cholecystectomy pathology and all underwent radical resection. Two patients were N1 on initial cholecystectomy pathology. Four were upstaged to N1 and two patients were upstaged to T3 after further surgery. Overall, 60 per cent patients with T2 disease had node positivity and 60 per cent were upstaged by further surgery. Eleven patients were diagnosed on imaging. Four of these patients were unresectable and six were either stage T3 or higher or node positive. Sixty per cent of T2 GBC was node positive and 60 per cent were upstaged with radical cholecystectomy. This finding supports the call for radical resection in patients with incidental diagnosis of T2 tumor on cholecystectomy. This study also emphasizes the role of radical surgery in accurate T staging.